2022
DOI: 10.1080/15384101.2022.2054096
|View full text |Cite
|
Sign up to set email alerts
|

MCL-1 is a clinically targetable vulnerability in breast cancer

Abstract: Pro-survival members of the BCL-2 family, including MCL-1, are emerging as important proteins during the development and therapeutic response of solid tumors. Notably, high levels of MCL-1 occur in breast cancer, where functional dependency has been demonstrated using cell lines and mouse models. The utility of restoring apoptosis in cancer cells through inhibition of pro-survival BCL-2 proteins has been realized in the clinic, where the first specific inhibitor of BCL-2 is approved for use in leukemia. A vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Also, Mcl1, a survival factor from the Bcl2 family, might be a direct or indirect target of miR342. 14 Mcl1 inhibitors can boost the efficacy of conventional treatments since this molecule is highly expressed in breast cancer, 23 especially the triple-negative type is highly dependent on this protein. 24 Interestingly, Mcl1 overexpression in breast cancer is more common than that of Bcl2 and Bcl2l1.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Mcl1, a survival factor from the Bcl2 family, might be a direct or indirect target of miR342. 14 Mcl1 inhibitors can boost the efficacy of conventional treatments since this molecule is highly expressed in breast cancer, 23 especially the triple-negative type is highly dependent on this protein. 24 Interestingly, Mcl1 overexpression in breast cancer is more common than that of Bcl2 and Bcl2l1.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the Elk-1 bond at the SRE site of the EGR1 promoter was sufficient for EGF-mediated EGR1 expression ( Gregg and Fraizer, 2011 ; Yang et al ., 2020 ). In breast cancer cells, EGF-induced activation of Elk-1 contributed to cell survival through Mcl-1 regulation ( Booy et al ., 2011 ; Winder and Campbell, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PEST domain of Mcl-1 interacts with AKT on the PH domain, activating the AKT signal pathway and collectively promoting the progression of lung cancer . Research has also indicated that the abnormal increase in levels of Mcl-1 can lead to drug resistance in targeted therapy for BC. − BH3 mimetics that target Bcl-2/Bcl-xL in combination with docetaxel or tamoxifen show promise in the treatment of BC. However, tumor cells often become insensitive to this treatment due to the high expression of Mcl-1.…”
Section: Research Progress Of Modulators Targeting Mcl-1 In Cancer Tr...mentioning
confidence: 99%